Overview and update on cytomegalovirus-associated anterior uveitis and glaucoma - Zifan Ye; Zifan Ye; Yumei Yang; Weishaer Ke; Weishaer Ke; Yuhang Li; Yuhang Li; Kaijun Wang; Kaijun Wang; Min Chen; Min Chen (Frontiers Media S.A., 2023)
Cytomegalovirus anterior uveitis is the most common ocular inflammatory disease caused by cytomegalovirus infection. It mainly occurs in middle-aged males with competent immunologic function, and the incidence is higher in Asia. The clinical manifestations vary from Posner-Schlossman syndrome and corneal endotheliitis to Fuchs uveitis syndrome, and are often accompanied by intraocular hypertension. Secondary glaucoma is a potentially blinding ocular complication with a pathogenesis that includes complicated immunological factors, intraocular inflammation, different types of angle abnormalities, and the administration of steroids, which may result in physical discomfort and visual impairment. Diagnostic tests, such as the polymerase chain reaction, optical coherence tomography, ocular microscopy, and confocal microscopy, might help in identifying anterior uveitis caused by other viruses. Combinations of antiviral medications and anti-inflammatory agents are effective treatments. If pharmacological therapy cannot reduce intraocular pressure or slow the progression of glaucomatous optic neuropathy, surgical intervention is required as a last resort.